Marketing Strategies for Responsible Tourism: Challenges and Opportunities - Vassileva, Bistra (Journal of Emerging Trends in Marketing and Management, 2017)
On a global scene, concerns about global warming, destruction of the environment, erosion of cultures and lifestyles, and millions of people still living in poverty, are increasing (International Centre for Responsible Tourism, 2012). The number of initiatives aimed at saving some part of the environment, or improving the living conditions for the world’s vulnerable people, increases steadily. According to the Ethical Consumer Markets Report (2012:2) markets for ethical goods and services have remained resilient throughout the economic downturn. Tourism is one of the world’s largest and fastest growing economic sectors. In 2015 the number of international tourist arrivals surpassed 1.2 billion with a forecast to reach 1.8 billion in 2030 according to the UNWTO. Within this continuing growth of tourism there is a growing trend and a raising consumer awareness for sustainable and responsible tourism. Since more than 90% of tourism companies in EU are small businesses, individual entrepreneurs or family houses, they do not have a capacity to exploit the opportunities offered by these new ‘green’ markets. Present paper provides results from a transnational study among micro and small tourist companies in seven EU countries - the Netherlands, Italy, Spain, Portugal, Northern Ireland, Bulgaria, and Malta. The research is conducted online and focuses on the attitudes toward CSR, the effect of CSR on company strategy, including marketing and brand strategy. Based on research results several implications about marketing strategies for responsible tourism initiatives launched by micro and small companies are presented.